Design, fabrication and measurements of planar Goubau lines from 0.75 THz to 1.1 THz - Cabello Sanchez, Juan (My University, 2017)
Terahertz (THz) waves have proven to possess a unique interaction with biomolecules, and therefore it’s interesting to study its influence using biosensors. Recent advances in heterodyne technology allow measuring on-wafer scattering parameters with Vector Network Analysers (VNA) up to 1.1 THz, which could be used for THz molecular spectroscopy. Compared to THz-Time Domain Spectroscopy (THz-TDS), this technique is expected to have greater sensitivity and dynamic range which would open new possibilities for near-field biomolecular spectroscopy. One possible set-up for near-field biosensing is using an on-wafer biosensor, which integrates microfluidic channels for the samples and electrical devices for the sensing. The Planar Goubau Line (PGL), a single conductor waveguide, has suitable properties for near-field on- wafer sensing since its geometry allows a correct sample deposition and a substantial part of the field travels on top of the substrate, where the samples will be located, thus increasing sensitivity. In this thesis, Planar Goubau Lines (PGL) have been designed, fabricated and measured for frequencies from 0.75THz to 1.1THz to be integrated as the electrical structure in a future on-wafer THz biosensor. Additionally, a design method for the layout of the Coplanar Waveguide (CPW) to PGL transition, needed for Ground-Signal-Ground (GSG) probe excitation, was developed to minimise reflections. Electromagnetic simulations were used for the design and analysis of the structures, and different software and port excitations were compared to achieve an accurate simulation environment. The importance of the choice of the substrate’s properties is investigated to increase the field on top of the substrate, reduce losses and limit the excitation of substrate modes. The fabrication process is described together with the VNA on-wafer S-parameter measurement set-up. To obtain conclusions for future optimisation of the structures, the fabricated structures were characterised, and different PGL widths and several CPW-PGL transitions were compared between 0.75 THz and 1.1 THz. In this frequency range, losses showed to be on average 5dB/mm and 13.3dB/mm for CPW and PGL, respectively. Despite the high losses per unit length happening at THz frequencies, the small size of the microfluidic channels allows its application in biosensing. The thesis shows that the transmission could be improved by eliminating the carrier wafer, limiting the use of the PGL to the sensing areas and shortening the CPW- PGL transitions. These guidelines would increase the signal-to-noise ratio for the sensor, increasing its potential to analyse THz-biomolecule interaction.
Keywords: Informations- och kommunikationsteknik; Livsvetenskaper; Nanovetenskap och nanoteknik; Elektroteknik och elektronik; Annan elektroteknik och elektronik; Övrig elektroteknik, elektronik och fotonik; Information & Communication Technology; Life Science; Nanoscience & Nanotechnology; Electrical Engineering, Electronic Engineering, Information Engineering; Other Electrical Engineering, Electronic Engineering, Information Engineering; Other electrical engineering, electronics and photonics